1996
DOI: 10.1002/nadc.19960440211
|View full text |Cite
|
Sign up to set email alerts
|

Theoretische Chemie 1995

Abstract: Kleine und mittlere Moleküle können dank neuer Ansätze wie der Dichtefunktional/Hartree‐Fock‐Hybridmethoden immer genauer berechnet werden. Tiefe Einblicke in Details des Reaktionsgeschehens bringt die Molekül‐ und Reaktionsdynamik durch das Wechselspiel von Experiment und Theorie. Aber auch Systeme von einigen zehntausend Atomen sind dank Kraftfeldmethoden kein Tabu mehr für Theoretiker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 144 publications
0
1
0
Order By: Relevance
“…Both groups concluded they had demonstrated that there was no justification for separate “classical” and “magnetic” concepts of aromaticity. Especially the papers by Schleyer have received considerable attention, and their conclusions were repeated by Grützmacher and Koch in widely disseminated commentaries. As these conclusions 7,8 seemed in direct contradiction to those reached independently in three of our research groups, we have carefully examined the evidence presented 7,8 that aromaticity is monodimensional.…”
mentioning
confidence: 99%
“…Both groups concluded they had demonstrated that there was no justification for separate “classical” and “magnetic” concepts of aromaticity. Especially the papers by Schleyer have received considerable attention, and their conclusions were repeated by Grützmacher and Koch in widely disseminated commentaries. As these conclusions 7,8 seemed in direct contradiction to those reached independently in three of our research groups, we have carefully examined the evidence presented 7,8 that aromaticity is monodimensional.…”
mentioning
confidence: 99%